2015
DOI: 10.1016/j.amper.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Phonaesthemes and sound symbolism in Swedish brand names

Abstract: Please cite this article as: AbelinÅ. Phonaesthemes and sound symbolism in Swedish brand names. Ampersand (2015), http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Furthermore -is there anything glittering in glwhen considering words like gloat, gloom or glove? Phonesthemes are said to exist in most languages, the question is whether they have a mere statistical background or not (e.g., Joseph 1994;Hutchins 1998;Abelin 1999Abelin , 2012Magnus 2001;Bergen 2004;Drellishak 2006;Ivanova 2006) or if the ranges of interpretations are due to phonic variation or ambiguity, depending on neighbouring sounds or the whole lexeme (Feist 2013). Data indicate that both aspects, natural/iconic and habitual information, interact.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore -is there anything glittering in glwhen considering words like gloat, gloom or glove? Phonesthemes are said to exist in most languages, the question is whether they have a mere statistical background or not (e.g., Joseph 1994;Hutchins 1998;Abelin 1999Abelin , 2012Magnus 2001;Bergen 2004;Drellishak 2006;Ivanova 2006) or if the ranges of interpretations are due to phonic variation or ambiguity, depending on neighbouring sounds or the whole lexeme (Feist 2013). Data indicate that both aspects, natural/iconic and habitual information, interact.…”
Section: Discussionmentioning
confidence: 99%
“…I will show that when one compares individual phonemes within the entire system, not just in isolation within a single lexical item, the same types of distributional tendencies found in spoken language phonology (Abelin 1999;Bergen 2004;Magnus 2001;Winter 2016) are seen in the phoneme inventory of ASL and Libras.…”
Section: Setting the Stagementioning
confidence: 80%
“…The short buildup of pressure and quickness of the air release in voiceless stops, allows for the construal of quickness, lack of invasiveness, and effectiveness in /p/ /t/ /k/ (Abel & Glinert 2008). Abelin (2015) found similar tendencies across marketing cases for multiple brands in Sweden, but found that fl-clusters, which evoke a sense of speed in Swedish, are also most statistically frequent in medicinal brand names than in standard Swedish. Poets, lyricists, and marketing experts at using these highly schematic sound-meaning associations in phonemes to activate relationships between the sounds and intended meanings.…”
Section: An Embodied Cognitive Phonologymentioning
confidence: 90%
“…consonant clusters) which have in common a certain element of meaning or function. For Abelin (1993), the relation between sound and meaning is often iconic or indexical, as well as symbolic. Lastly, Abelin (1993) GEMA Online ® Journal of Language Studies Volume 17(3), August 2017August http://doi.org/10.17576/gema-2017August -1703 eISSN : 2550-2131 ISSN: 1675-8021 140 concluded that (the) sound symbolism referred to the general phenomenon of motivated relations between sound and meaning, including onomatopoeia.…”
Section: Introductionmentioning
confidence: 99%
“…For Abelin (1993), the relation between sound and meaning is often iconic or indexical, as well as symbolic. Lastly, Abelin (1993) GEMA Online ® Journal of Language Studies Volume 17(3), August 2017August http://doi.org/10.17576/gema-2017August -1703 eISSN : 2550-2131 ISSN: 1675-8021 140 concluded that (the) sound symbolism referred to the general phenomenon of motivated relations between sound and meaning, including onomatopoeia. Recent studies have also investigated the linguistic aspects of onomatopoeia, as was conducted by Carling and Johansson (2015) who examined the German-motivated language changes, as part of the branch of Indo-European languages.…”
Section: Introductionmentioning
confidence: 99%